Education for Sustainabilty (EfS) for Indonesian Higher Education: A Literature Review - Nuur Insan Tangkelangi (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
Indonesia currently faces various problems in multiple aspects: social, economic, and environment. The problems become complex because they are interconnected each other. Due to this complexity, it is crucial to find a solution to overcome those problems. The concept of sustainability focusing on creating sustainable development in various aspects (social, economic, and environment) can be appropriate to be adapted. Then, to internalize the concept into a country, education is the best medium since it can build societies’ awareness on the importance of this concept and change their perceptions, attitudes, and behaviours. The internalization of sustainability concept in education is called Education for Sustainability (EfS) which adapts sustainability in institution management and curriculum. To show the opportunities of EfS implementation in Indonesia, challenges and solutions of EfS implementation in other countries are firstly discussed in this article followed by how EfS can be applied in Indonesian universities. At the end, conclusion and recommendations related to EfS implementation in Indonesian universities are proposed.